Effects of gamma irradiation on microbial of white sandwich bread - Hamza, Muhammad Hanif; Sayed, Inayatullah Shah; Abu Bakar, Ibrahim (Research Publish Journals, 2016)
Daily consumption of bread as staple food is enormous. However, the spoilage of the bread is a common problem and mainly caused by microbial. This study investigates the effects of gamma irradiation on microbial of white sandwich bread. Three different brands were irradiated using gamma radiation doses of 0.0, 0.2, 0.3, 0.4 and 0.5 kGy. Results show that 0.2 to 0.5 kGy gamma radiation exposure to the bread has the potential of eliminating or at least minimizing the ecology of spoilage-causing microorganisms in the bread. It is concluded that gamma irradiation could serve as an effective method in extending the shelf life of white sandwich bread.